China's techno-warriors national security and strategic competition from the nuclear to the information age - Feigenbaum, Evan A. (Stanford University Press, 2003)
The book tells the story of how and why the Chinese military came to play such a powerful role in the country's economic and institutional development. It focuses on four issues: Chinese views of technology since 1950, the role of the military in China's political and economic life, the evolution of open and flexible conceptions of public management in China, and the technological dimensions of the rise of Chinese power.